EFFECT OF SEED SOAKING WITH GA3 ON EMERGENCE AND SEEDLING GROWTH OF CORN UNDER SALT STRESS - & Ali, Hamza (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Soaking seeds with gibberellic acid improves germination and may consider as a solution for reduce negative effects of salt stress. Therefore, an experiment was carried out in shaded area belong to Agriculture College, University of Baghdad during fall and spring seasons 2012-2013 to test effect of seeds soaking in GA3 on emergence and seedling growth of corn under salt stress. First factor was two levels dry seeds and soaked seeds in 300 ppm concentration of GA3 for 24 hours. Second factor was five levels (0, 1000, 2000, 3000 and 4000 ppm NaCl). Randomize complete block design (RCBD) was used with four replications. Results showed significant superiority of soaked seeds in GA3 gave best values for last day of emergence, time it takes for the emergence, mean of emergence time, coefficient velocity of emergence, emergence rate index, seedling length and seedling dry weight during both seasons. Results showed increased negative effects with increasing of NaCl concentration for same attributes above except time it takes for the emergence during both seasons. Content of leaves of proline acid was increased with increasing of NaCl concentration. Results showed significant interaction between treatment of soaked seed in GA3 and treatment of 0 ppm concentration of NaCl compared with interaction between treatment of dry seeds and treatment of 4.000 ppm concentration of NaCl, has given best values for emergence rate index and seedling dry weight during both seasons. Significant correlation positive and negative was found between most those attributes. It can be conclude that soaking of seeds in GA3 improved emergence and seedling growth of corn under salt stress. We recommend soaking corn seeds in 300 ppm concentration of GA3 for 24 hours before planting in salty lands.